"Flakka" use among high school seniors in the United States. (1st March 2019) - Palamar, Joseph J.; Rutherford, Caroline; Keyes, Katherine M.
Highlights: We examined self-reported past-year Flakka use among high school seniors in the US. Having parents with less than a high school education increased odds for use. Flakka users were more likely to use the 11 other psychoactive drugs examined. Flakka users were more likely to use more drugs and at higher frequency. Prevention needs to focus on users of multiple illegal drugs. Abstract: Background: Use of synthetic cathinones, commonly referred to as "bath salts", has been associated with tens of thousands of emergency department visits in the US; however, few national studies have estimated prevalence of use and we know very little about use among adolescents. In this study we estimate prevalence and correlates of use of "Flakka" (alpha-PVP), a highly-potent "bath salt" associated with at least 80 deaths in the US. Methods: We analyzed data from the 2016/2017 Monitoring the Future study, which surveyed a nationally representative sample of high school seniors in the US (n = 3786). Bivariable and multivariable models were used to determine demographic and drug-related correlates of use. Results: Overall, 0.8% (95% CI: 0.5–1.2) of high school seniors in 2016/2017 is estimated to have used Flakka in the past year. Students whose parents have less than a high school education were at higher odds for use (aOR = 4.12, 95% CI: 1.00–16.94). Flakka users reported high prevalence of use of other drugs, particularly synthetic cannabinoids (85.6%), ketamine (72.3%), marijuana (59.1%), and GHB (47.5%). Flakka use was also associated with use of a higher number of other drugs and higher frequency of use of other drugs, with 51.7% using 4–12 other drugs and 22.4% using 4–12 other drugs >6 times. Conclusions: Students who use multiple drugs are elevated risk for Flakka use, suggesting synthetic cathinone use alone is rare and the use of multiple substances may compound adverse effects of these drugs. Socio-economic disparities are concerning given reduced access to prevention and intervention.